1976
DOI: 10.1021/j100559a018
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical calculation of strong complex formation by the hydroperoxo radical: hydroperoxo.cntdot.water and hydroperoxo.cntdot.ammonia

Abstract: Exploratory ab initio calculations using a minimal basis set support the existence of the 02• 20 and H02• NH3 complexes, as proposed earlier by experiment. For the minimum energy configurations having H02 as the H donor within a linear H-bond structure, electronic stabilization energies of 9.1 and 12.0 kcal/mol are calculated for H02-H20 and HC^-NHb, respectively, compared with 5.3 kcal/mol for (H20)2. Values of AH°a nd AS°for the complex formations are estimated and found consistent with available experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 2 publications
(3 reference statements)
5
32
0
Order By: Relevance
“…To make such calculations more practical, stochastic optimizations using classical potential energy functions can be performed ®rst to determine good starting points for the quantum optimizations. [24] performed an ab initio calculation of the HO 2 H 2 O complex using an STO-3G basis set. Their study did not use a fully optimized structure.…”
Section: Introductionmentioning
confidence: 99%
“…To make such calculations more practical, stochastic optimizations using classical potential energy functions can be performed ®rst to determine good starting points for the quantum optimizations. [24] performed an ab initio calculation of the HO 2 H 2 O complex using an STO-3G basis set. Their study did not use a fully optimized structure.…”
Section: Introductionmentioning
confidence: 99%
“…[87] The results of Nelander's experimental study [82] are in good agreement with quantum chemical calculations. [88][89][90][91] Among the theoretical works, it is believed that the most reliable results are those of Aloisio and Francisco, [90] where calculations were carried out at the MP2/6-311 + + G(2df,2p) level of theory, and those of Aloisio et al [91] (calculations of the excitation energies of the three lowest electronic states of HOOC and H 2 O·HOOC using CASSCF and MRCI methods). It was found that the most favorable conformation of the complex is an asymmetric five-membered cyclic structure [···O(H)ÀH···OÀOÀH···] with one of the water hydrogen atoms located out of the molecular plane (Figure 12).…”
mentioning
confidence: 99%
“…This complex H 2 0. H0 2 has been studied by Hamilton [32], but because of technology and theory limitations at that time, the calculation remained at the SCF level and the geometry was only partially optimized.…”
Section: Chapter IIImentioning
confidence: 99%
“…Previous work [32] on HzO· HO z performed a point-by-point partial geometry optimization and derived an almost planar structure (the HzO plane was 4°out of the HO z plane). In our studies, first we tried to determine the complex symmetry.…”
Section: Geometries Of Hzo H02 and Hzo Hzomentioning
confidence: 99%
See 1 more Smart Citation